The use of saccharides as a carbon source in the method of boron carbide synthesis from polymeric precursors-A review - Karaahmet, Oguz; Cicek, Bugra (TAYLOR & FRANCIS INC, 2025)
Boron carbide (B4C) is generally produced by the traditional carbothermic reduction method. However, low-cost methods have emerged as alternatives to the current carbothermic reduction method, where the leading approach is synthesis using polymeric precursors. The synthesis of B4C using polymeric precursors can be carried out at lower temperatures (<1600 degrees C). Boric acid (H3BO3) and boron oxide (B2O3) are used as the boron sources, whereas the carbon source consists of polyols, such as saccharides. Saccharides have been preferred as a carbon source because of their easy accessibility and cost-effectiveness, and innovative approaches have been presented in many research works. In this review, the raw material sources and research on the condensation, pyrolysis, and synthesis conditions are described under the subheadings of simple sugars (monosaccharides) and complex sugars (disaccharides and polysaccharides). Also, the B4C particles produced are evaluated in terms of morphology, purity, and size.
Keywords: B4C; polymeric precursor; carbon source; saccharides; carbothermic reduction; CARBOTHERMAL REDUCTION; B4C CERAMICS; TEMPERATURE; POWDER; RESISTANCE; MORPHOLOGY; NANOPARTICLES; COMPOSITES; PARTICLES; BEHAVIOR; Chemistry; Science & Technology - Other Topics